ANALYSIS OF MERDEKA CURRICULUM LEARNING DEVELOPMENT OF ISLAMIC EDUCATION TEACHING MATERIALS IN ELEMENTARY SCHOOL - Mohd Hofifi; Muh. Fiqh Shofiyul Am; Muhammad Yusron Maulana el-yunusi; Tri Wahyudi Ramdhan (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2023)
The purpose of this study is to analyze the Merdeka Curriculum Learning (Merdeka Curriculumstudy) in the subject of pie (Islamic Religious Education) and moral character applied at Elementary School. the play goals of the Independent curriculum is to prepare students for spiritual maturity, wisdom, and noble character. this research uses qualitative libraries research method and involves the analysis of content description. Data is collected through observation, in- depth interview, and documentation study. The results of the analysis indicate that the Independent learning achievements formulations contains comprehensive competencies and scope of materials in the form of narratives that are adjusted to the developmental stage of students in phase E for grade 10. The ideal learning objective formulation consists of two components: first, attitude, knowledge, and skills competencies; Second, the content, which is core knowledge. The learning objective flow formulations descriptions the coverage and stages of learning from the beginning to the end of the phase in a linear manner